Investigating the dissolution of soil phosphate - Barrow, N. J.; Debnath, Abhijit; Sen, Arup (Plant and soil, 2023)
Aims The effectiveness of phosphate fertilisers decreases with increasing period of reaction. One explanation for this is that the phosphate (P) has changed its chemical form. Evidence for this is provided by fractionation schemes which include extraction with alkali, followed by extraction with acid. Our aim was to test whether alkali and acid extracted different moieties and to test their ability to reflect changes in phosphate form over time. Methods We measured the effect of period of reaction between P and an iron (hydroxy)oxide (goethite), an aluminium oxide, and a soil, using two methods. These are: extraction with acid and extraction with alkali. Results Extraction of P by acid was similar to extraction by alkali. This is not consistent with the idea that they extract different kinds of phosphate. With increasing period of reaction, more iron and more aluminium needed to be dissolved in order to dissolve the same amount of P. The rate of dissolution of iron and of aluminium decreased with increasing period of reaction with phosphate. Conclusions Our results are consistent with diffusion of P into the reacting materials rather than formation of different chemical forms. We think the increased resistance to disolution occurred because phosphate diffused into defects and repaired them. Fractionation methods reflect increasing vigour of extraction rather than the presence of separate forms.